2007
DOI: 10.5194/acp-7-6047-2007
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the meteorological radiation model during the solar eclipse of 29 March 2006

Abstract: Abstract.Various solar broadband models have been developed in the last half of the 20th century. The driving demand has been the estimation of available solar energy at different locations on earth for various applications. The motivation for such developments, though, has been the ample lack of solar radiation measurements at global scale. Therefore, the main goal of such codes is to generate artificial solar radiation series or calculate the availability of solar energy at a place.One of the broadband model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Temperature, solar irradiance, relative humidity, wind and cloudiness within the surface layer are among the most common meteorological parameters explored by previous studies of solar eclipses (Fernandez et al, 1993(Fernandez et al, , 1996Hanna, 2000;Psiloglou and Kambezidis, 2007;Emde and Mayer, 2007;Kazadzis et al, 2007). The drop in surface temperature during a solar eclipse is of broad interest and becomes noticeable when the sun is about half covered (Anderson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, solar irradiance, relative humidity, wind and cloudiness within the surface layer are among the most common meteorological parameters explored by previous studies of solar eclipses (Fernandez et al, 1993(Fernandez et al, , 1996Hanna, 2000;Psiloglou and Kambezidis, 2007;Emde and Mayer, 2007;Kazadzis et al, 2007). The drop in surface temperature during a solar eclipse is of broad interest and becomes noticeable when the sun is about half covered (Anderson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Using these two input files, the AMY weather files were packed by the DOE-2.1e program. 18 and 2418 CDD 10 . A ten story standard office building with 2323 m 2 of floor area on each floor was created.…”
Section: Global Solar Radiation Results Obtained Using the Three Solamentioning
confidence: 99%
“…Since the entire calculation process is too complicated for this research, only the main equations are shown here. For more detail, please see the study conducted by Psiloglou and Kambezidis [18].…”
Section: Meteorological Radiation Model (Mrm)mentioning
confidence: 99%
“…The transmittances from gases are used by both methods (clear and cloudy cases) to account for the absorption of gas molecules. They are parametrized empirically according to reference [55] as follows…”
Section: Aerosol Optical Depth and Speciationmentioning
confidence: 99%
“…Coefficients a, b, c, and d used to compute the shortwave gases transmittances; from references[55][56][57][58].…”
mentioning
confidence: 99%